Pemidanaan Kasus Pemerkosaan Berantai oleh Agus Buntung: Tinjauan Hukum Pidana Indonesia - Nikmatul Wardiah Pulungan; Wizalkarnaen Hasibuan; Ilham Kurniawan Syahputra; Muhammad Afdul Soleh; Adrina Fauza (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
The case of serial rape committed by I Wayan Agus Suartama, a man with a disability, raises complex debates about punishment and the rights of persons with disabilities. This research aims to analyze the criminalization of the criminal case of rape from the perspective of criminal law and the rights of persons with disabilities in Indonesia. The research method used is juridical-normative research by analyzing cases and interviews with legal experts and disability activists. The results showed that the criminalization of the case had not been adequately considered and considered the rights of persons with disabilities and needed improvement in terms of accessibility, education and awareness about disability. This research recommends improvements to criminal law and policies for the protection of persons with disabilities to promote social justice and equality.